Should day care be subsidized? - David Domeij; Paul Klein (Stockholm School of Economics, The Economic Research Institute (EFI), 2010)
In an economy with distortionary taxes on labor, can subsidies on day care, financed by an increase in taxes, raise welfare by encouraging women with small children to work? We show, within a heterogeneous-agent life-cycle framework, that the Ramsey optimal policy consists in equalizing consumption/leisure wedges over the life cycle and across agents. A simple way to implement this is to make day care expenses tax deductible. Calibrating our model to Germany, we find that tax deductibility for day care expenses leads to an approximate doubling of labor supply for both married and single mothers with small children. The overall welfare gain from optimal reform corresponds to a 1.0 percent increase in consumption.
Keywords: E13; J13; 330; Female labor force participation; Germany; day care subsidies; Weibliche Arbeitskräfte; Familienleistungsausgleich; Wohlfahrtseffekt; Lebenszyklus; Deutschland